Respuesta :

Hello!

The answer to your problem is: [tex]x=1/13[/tex]

Simplify both sides of the equation

[tex](2)(-4x)+(2)(1)=(2/3)(x)+(2/3)(2)[/tex] [tex](Distribute)[/tex]

[tex]-8x+2=2/3x+4/3[/tex]

Subtract 2/3x from both sides

[tex]-8x+2-2/3x=2/3+4/3-2/3x[/tex]

[tex]-26x+2=4/3[/tex]

Subtract 2 from both sides

[tex]-26/3x+2-2=4/3-2[/tex]

[tex]-26/3=-2/3[/tex]

Multiply both sides by 3/(-26)

[tex](3/26)*(-26/3x)=(3/-26)*(-2/3)[/tex]

Get your answer

[tex]x=1/13[/tex]

Hope This Helps!

ACCESS MORE